Expounding nested case control studies in the year of COVID-19: a scoping review and sub group meta-analysis - Tapnikar, Lata Ajay; Joshi, Mohan P.; Soni, Antara A.; Saoji, Ajeet V. (International Journal Of Community Medicine And Public Health, 2022)
Nested case control studies (NCCS) are mainly a type of cohort study due to its forward direction and temporality. This design is done only under two circumstances. a. disease must be new and rare in the population b. The diagnostic test must be fairly expensive. Thus, this study design is defined as ‘a small case control study nested within a big cohort study’. The paper has expounded existing literature on nested case control studies by using scoping review and meta-analysis on hypertension sub-group. The data was systematically searched with following databases: Medline, NLM which had free articles and Google scholar. The aim of the study was to scope review of English language research papers from May 2020 to May 2021. 86 studies were excluded and 9 studies were selected after reviewing the title and abstract of 209 studies based on the PRISMA. The research has made a unique contribution, in a resource crunched setting, in expounding the study design implementations by lending critical viewing, theoretical revision and, new perspectives on use of nested case control studies in field settings.